Avaliaç\~ao de priorizaç\~oes para expans\~ao da rede de acesso à banda larga nos municípios brasileiros - Alexandre Ywata de Carvalho; Mário Jorge Cardoso de Mendonça; José Jaime da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This study aims to present a model for economic evaluation of the expansion of the broadband network for the Brazilian municipalities. This is done taking into account not only the economic return, but also the cost of expanding the network. Return is calculated from three criteria of prioritization: size of population, HDI, and potential market. Once one of these criteria is chosen, the effect on certain variables of interest, such as the effect on the product, access to the poorest population, etc., is estimated. To determine the potential demand of broadband, we estimated model combining two databases: PNAD 2015 and Census 2010. The effect of broadband on municipal GDP was obtained using the panel data model. To evaluate the cost to expand network we the applied the solution of the minimum generating tree from the graph theory. It was observed that the criterion based on the potential market is the alternative that generates greater economic return. Also the results obtained based on the size of the population are close to this one, whereas the prioritization by the municipal HDI is the criterion that presents the worst performance that penalizes the poor and the extremely poor population.
Keywords: C21; O33; 330; broadband; backhaul; graph theory; minimum spanning tree; logit regression; panel data